Nucleação, crescimento de cristais, relaxação e escoamento viscoso em vidros de diopsídio e diborato de lítio - Cassar, Daniel Roberto (Universidade Federal de São Carlos, 2014)
Heated glasses undergo a variety of kinetic processes, such as crystallization, relaxation and viscous flow, that are very important both scientifically and technologically. In this work, we measured and rigorously analyzed these processes according to several models and theories, for two glass compositions: diopside (CaO MgO 2 SiO2) and lithium diborate (Li2O 2 B2O3). These analyses addressed the following questions: which viscosity model better describes the experimental data? Which viscosity model better describes the structural relaxation kinetics bellow the glass transition temperature? Does the decoupling between crystallization and viscous flow kinetics occur for the studied materials, as reported in the literature for lithium disilicate? The results showed that the MYEGA viscosity model described well both viscous flow and structural relaxation data. Moreover, our results point towards an explanation for the breakdown between crystallization and viscous flow kinetics: it is a phenomenon in which the crystal growth structural units are able to move without cooperative rearrangements if the viscosity is above 5,6(6) 103 Pa s. With our results for lithium diborate, we confirmed Kauzmann s resolution for his own paradox: this glass fully crystallizes before achieving a metastable equilibrium state when kept at the Kauzmann s temperature. This means that such glass cannot undergo the ideal glass transition . These findings are useful for technological processes such as glass annealing, new glass-ceramic microstructure design, and glass making.
Nucleation, crystal growth, relaxation and viscous flow in diopside and lithium diborate glasses
Keywords: Vidro; Cristalização; Viscosidade; Relaxação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA